Dynamic circular causation model in poverty alleviation: Empirical evidence from Indonesia. Issue 3 (8th August 2016) - Mariyanti, Tatik; Mahfudz, Akhmad Affandi
Abstract : Purpose: This paper aims to unveil the impact of government policy, socio-economic variable, Zakat Infaq Shadaqah (ZIS) and financing of Baitul Maal wat Tamwil (BMT) toward severe problem of poverty in Indonesia. Design/methodology/approach: The paper considers dynamic circular causation model to produce proper solution on Indonesian style of poverty that hitherto remain unresolved. Findings: All variables including ZIS, government policy, socio-economic variable and BMT financing have an impact toward poverty reduction. Research limitations/implications: This paper confined to the scope of poverty that occurred in Indonesia only, and therefore all variables and literatures derived from Indonesian pedigree on poverty. Practical implications: This paper implies that government policy will be shifted toward focusing on extending subsidy for rural society to uplift their income by involving in more real sector. Originality/value: This paper considered to be scarce as focusing only for Indonesian style of poverty by using dynamic circular causation model as a solution.